2018
DOI: 10.1101/255364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicolor single particle reconstruction of protein complexes

Abstract: 13Single-particle reconstruction (SPR) from electron microscopy images is widely used in 14 structural biology, but lacks direct information on protein identity. To address this limitation, we 15 developed a computational and analytical framework that reconstructs and co-aligns multiple 16 proteins from 2D super-resolution fluorescence images. We demonstrate our method by 17 generating multi-color 3D reconstructions of several proteins within the human centriole and 18 procentriole, revealing their relative lo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…After training with these images, our network converged on a central torus for the CEP152 complex (Figures 10,11). This inferred structure is consistent with the confirmed structure of this protein complex (Sieben et al, 2018;Kim et al, 2019).…”
Section: Smlm Dataset Of the Cep152 Complexsupporting
confidence: 89%
See 3 more Smart Citations
“…After training with these images, our network converged on a central torus for the CEP152 complex (Figures 10,11). This inferred structure is consistent with the confirmed structure of this protein complex (Sieben et al, 2018;Kim et al, 2019).…”
Section: Smlm Dataset Of the Cep152 Complexsupporting
confidence: 89%
“…The first dataset was a super-resolution (STORM) microscopy data-set of CEP152, obtained and analysed as described in Sieben et al (2018). The structure of this centro-symmetric complex has been fitted with a toroid and found to be 400 nm in diameter (Sieben et al, 2018), which subsequent work confirmed (Kim et al, 2019). This yielded a list of localisations for each identified CEP152 structure which were reconstructed localisations into 2D images, rendering with a Gaussian.…”
Section: Experimental Data From Biological Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Super-resolution microscopy, and specifically Single-Molecule Localization Microscopy (SMLM) (Betzig et al, 2006;Hess et al, 2006;Rust et al, 2006), achieves nanometer resolution combined with molecular specificity, and has the potential to bridge this gap in our knowledge. It has been used to get structural insights into the organization of multi-protein complexes such as the nuclear pore complex (Szymborska et al, 2013), the endocytic machinery (Mund et al, 2018;Sochacki et al, 2017), centrioles (Sieben et al, 2018) or synaptic proteins (Dani et al, 2010). In this study, we use SMLM to determine the location of key proteins and their copy numbers with single kinetochore resolution in S. cerevisiae cells (Figure 1).…”
Section: Introductionmentioning
confidence: 99%